Anterior cruciate ligament deficiency causes brain plasticity: A functional MRI study - Kapreli, E.; Athanasopoulos, S.; Gliatis, J.; Papathanasiou, M.; Peeters, R.; Strimpakos, N.; van Hecke, P.; Gouliamos, A.; Sunaert, S. (The American Journal of Sports Medicine, 2009)
The mechanoreceptors located in anterior cruciate ligament (ACL) constitute an afferent source of information toward the central nervous system. It has been proposed that ACL deficiency causes a disturbance in neuromuscular control, affects central programs and consequently the motor response resulting in serious dysfunction of the injured limb.